Primary study on application of cell-free fetal DNA (cffDNA) in non-invasive prenatal testing of β-thalassemia - Van Bo Em, Trinh; Van Thong, Nguyen; Thi Thanh Kieu, Nguyen; Thi Thu Hang, Đo (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 1SDO - 10.25073/2588-1140/vnunst.4546, 2017)
β-thalassemia is a common autosomal recessive disorders, caused by mutations in the β-globin gene. It severely influences the physical and mental development of affected children and place an immense burden of care and treatment on the family and society. Therefore, the prenatal screening of β-thalassemia to control its increase in the community is anessential part of preventive genetics. Currently, besides traditional prenatal diagnostic tests that requires invasive sampling techniques such as amniocentesis or chorionic villous sampling (CVS), the use of cffDNA for non-invasive prenatal testing of β-thalassemia is a new, safer, and more effective direction. In this study, we extracted and enriched the percent of cffDNA in the maternal peripheral blood as well as optimized AS-PCR to detect three most common β-thalassemia mutations CD17, CD26, and CD41/42. Presence or absence of the paternal mutant allele was then correctly determined in all of 7 cases compared to fetal genotyping that determined with amniocentesis.